Детектирование магнитных наночастиц в жидкой среде акустомагнитным методом. - Бондаренко, И. С.; Бондаренко, С. И.; Аврунін, О. Г. (ХНУРЕ, 2019)
The technique and results of experiments on the registration of magnetic nanoparticles in a colloidal solution using the combined effect of ultrasound and a constant magnetic field are presented. The possibility of using this technique to control the content of magnetic nanoparticles in a biological environment is discussed. The proposed work is aimed at solving one of the problems arising in the implementation of targeted drug delivery to the pathological area of the human body. This problem is operational (i.e., in a short time) ensuring the high accuracy of the in vivo determination of drug concentrations in the target area.
Keywords: наночастицы; среда жидкая; метод акустомагнитный